Influência da turbidez da água sobre a mobilidade de peixes : um estudo meta-analítico - Rodrigues, Jean Nascimento (2021)
Increased turbidity in aquatic environments directly impacts the ability of fish to use visual stimuli as a source of information. In general, fish compensate for the reduced probability of finding prey under reduced underwater visibility by increasing the distance traveled and/or the time spent in active swimming. However, there are also studies in the literature suggesting that the activity level of some fish populations is not altered by variations in turbidity levels. In this study, we conducted a systematic review and meta-analysis on the effect of turbidity on fish mobility. We tested the hypothesis that turbidity increases the swimming activity of piscivorous and non-p piscivorous fish species. Furthermore, controlling for the dependence between effect sizes and phylogenetic relationships among fish species, we explored possible sources of heterogeneity in turbidity effect sizes on fish mobility across studies, evaluating as moderators: body size, eye size and trophic position of fish and the turbidity range used in the studies. We found a null effect of turbidity on fish mobility and a significant variation in the calculated effect size between studies, mediated mainly by the turbidity range investigated in the studies. On the other hand, the calculated effect size was not influenced by body size, eye size, and trophic position of the fish. We found that different fish species have distinct contributions to the calculated effect size, which may indicate that the effect size of turbidity on fish mobility depends on some fish characteristics. Among such characteristics, the life-history adaptation of fishes to turbid water conditions seems to be decisive, because individuals adapted to turbid environments are less affected by increases in turbidity than individuals adapted to clear water environments, showing that the recent experience of fishes may be a source of intraspecific variability in the response of fishes to increases in turbidity. Finally, we also observed a geographic gap in the conduct of studies in (sub)tropical climates, as most studies have been conducted in the northern hemisphere, studying fish adapted to temperate climates. Our findings help us understand how changes in water transparency (natural or human-mediated) can directly or indirectly alter fish behavior, and reveal that some populations are more susceptible to local extinction, while others are able to cope with changing environments and persist.